2005
DOI: 10.1194/jlr.m400325-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothyroidism on mammary and liver lipid metabolism in virgin and late-pregnant rats

Abstract: Untreated maternal hypothyroidism (hypoT) has serious consequences in offspring development that may result from the effect on lactation of maternal metabolism dysfunction. We studied the effects of prolonged propylthiouracyl (PTU)-induced hypoT (0.1% PTU in drinking water starting 8 days before mating until day 21 of pregnancy or for 30 days in virgin rats) on liver and mammary lipid metabolism and serum lipid concentrations. In virgins, hypoT reduced hepatic mRNAs associated with triglyceride (TG) and choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 61 publications
(49 reference statements)
1
37
0
4
Order By: Relevance
“…Although there is no evidence of a direct or indirect regulation of PGE2 by thyroid hormones, there is sufficient information demonstrating that the circulating concentration of PGE2 is dependent on cholesterol-low density lipoprotein (LDL) levels (Habenicht et al 1986). We have recently shown that circulating LDL-cholesterol is elevated in hypothyroid rats regardless of the reproductive state (Hapon et al 2005), and this factor may be linked with the observed elevated serum PGE2. Moreover, hypercholesterolemia may directly influence P 4 production, since in vivo and Figure 5 Effect of PTU treatment on luteal mRNA abundance of COX2, iNOS and PGF2aR on days 19 (G19) and 21 (G21) of pregnancy and 2 of lactation (L2).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence of a direct or indirect regulation of PGE2 by thyroid hormones, there is sufficient information demonstrating that the circulating concentration of PGE2 is dependent on cholesterol-low density lipoprotein (LDL) levels (Habenicht et al 1986). We have recently shown that circulating LDL-cholesterol is elevated in hypothyroid rats regardless of the reproductive state (Hapon et al 2005), and this factor may be linked with the observed elevated serum PGE2. Moreover, hypercholesterolemia may directly influence P 4 production, since in vivo and Figure 5 Effect of PTU treatment on luteal mRNA abundance of COX2, iNOS and PGF2aR on days 19 (G19) and 21 (G21) of pregnancy and 2 of lactation (L2).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA levels of 7 -hydroxylase are not modified by pregnancy or by hypothyroidism. In addition, the LDL receptor mRNA, a factor involved in cholesterol uptake that is increased during late gestation, is decreased in the pregnant hypothyroid rats, contributing to the increased circulating (LDL+VLDL)-C (Hapon et al, 2005). It is well known that hypothyroidism increases cholesterol through an enhancement of LDL.…”
Section: Liver and Mammary Lipids In Pregnancymentioning
confidence: 99%
“…Changes in thyroid state indirectly modify the biosynthesis of cholesterol by its effects on metabolism and on the coefficient of intestinal absorption of cholesterol (Mathe & Chevallier, 1976). The mRNA levels of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, which is the rate-limiting enzyme for de novo cholesterol biosynthesis, is increased in the liver during late gestation, but the change of 3-hydroxy-3-methylglutarylcoenzyme A reductase is not modified by hypothyroidism (Hapon et al, 2005). The mRNA levels of 7 -hydroxylase are not modified by pregnancy or by hypothyroidism.…”
Section: Liver and Mammary Lipids In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations